EFEKTIVITAS LABELISASI HALAL USAHA KIPANG DITINJAU DARI EKONOMI ISLAM (STUDI KASUS USAHA KIPANG DIAN KELURAHAN PANYABUNGAN II) - Siti Kholijah (EKSYA : Jurnal Ekonomi Syariah, 2021)
This study aims to find out how the Effectiveness of the Halal Label for Kipang Dian Business Products and how the Islamic Economic Review is on the halal labeling of Kipang Dian businesses. The data collection technique carried out by the author is by interviewing the owner of the Kipang Dian Business and observations made on retail traders and consumers, as well as the addition of reading books and also other sources related to the research title. Furthermore, the results of the study were analyzed through a descriptive analysis method which described how the level of effectiveness of Halal Labeling for Kipang Dian Business Products and how the Islamic Economic Review of Kipang Dian's business halal labeling. The data used in this study are primary data and secondary data with research subjects consisting of business owners, employees, traders and consumers. The results showed that the effectiveness of the Halal Label for Kipang Dian Products was influenced by 4 factors, namely product, price, location and promotion. Based on the results of the study, the use of halal labeling on Kipang Dian is very beneficial for Kipang Dian owners themselves as well as for traders/agents because the existence of a halal label on Kipang Dian can increase consumer trust and satisfaction in Kipang Dian than other kipang which do not there is a halal label. From an Islamic economic point of view, the use of halal labeling on kipang dian businesses can provide economic benefits for business actors, consumers and the government. It also provides opportunities for entrepreneurs that are much better and more widely open and are products that comply with halal in accordance with Islamic law.